2006
DOI: 10.2139/ssrn.766465
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Sin: The Effects of Social Norms on Markets

Abstract: Abstract:We provide evidence for the effects of social norms on markets by studying "sin" stocks-publicly traded companies involved in producing alcohol, tobacco, and gaming. We hypothesize that there is a societal norm against funding operations that promote vice and that some investors, particularly institutions subject to norms, pay a financial cost in abstaining from these stocks. Consistent with this hypothesis, we find that sin stocks are less held by normconstrained institutions such as pension plans as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Second, Institutional investors are more inclined to participate proactively in corporate governance [35,36] and are concerned about the sustainability and long-term prospects of the company [37]. Institutional investors judge whether a company is worthy of investment based on the environmental information disclosed by the company [38,39], and a high level of corporate disclosure has a higher profitability and social status [40]. Institutional investors have information advantages because they have diversified information channels, rich management experience, and a professional team of analysts who can effectively search, screen, and process information [41], which also enables institutional investors to obtain the environmental information of enterprises in a timely manner, identify the environmental problems of enterprises early, and urge managers to make corrections [42].Wang et al [43] found that institutional investors have the ability and motivation to influence corporate decision making based on their own traits and strengths, and tend to support strategic decisions of corporate social responsibility.…”
Section: A Summary Of Relevant Research On Institutional Investors' S...mentioning
confidence: 99%
“…Second, Institutional investors are more inclined to participate proactively in corporate governance [35,36] and are concerned about the sustainability and long-term prospects of the company [37]. Institutional investors judge whether a company is worthy of investment based on the environmental information disclosed by the company [38,39], and a high level of corporate disclosure has a higher profitability and social status [40]. Institutional investors have information advantages because they have diversified information channels, rich management experience, and a professional team of analysts who can effectively search, screen, and process information [41], which also enables institutional investors to obtain the environmental information of enterprises in a timely manner, identify the environmental problems of enterprises early, and urge managers to make corrections [42].Wang et al [43] found that institutional investors have the ability and motivation to influence corporate decision making based on their own traits and strengths, and tend to support strategic decisions of corporate social responsibility.…”
Section: A Summary Of Relevant Research On Institutional Investors' S...mentioning
confidence: 99%
“…Li, Li and Zhang (2019b) analyzed the data of the top 500 A-share listed companies with the most brand value in China, and showed that corporate social responsibility had a negative impact on brand value, while high-tech innovation level could weaken the negative effect of corporate social responsibility on brand value. Meanwhile, if the company's innovation investment is not appropriate, it will offset the positive impact of ESG behavior (Kacperczyk & Hong, 2018), which has a negative impact on financial Y. F. Li Open Journal of Business and Management performance (Serafeim, 2018;Oikonomou et al, 2012). Liao et al (2021) found that the positive impact of CSR on corporate performance in China was different in enterprises with different financial constraints, while innovation investment had a negative impact on the relationship between CSR and performance.…”
Section: Introductionmentioning
confidence: 99%